2019
DOI: 10.4274/tjps.galenos.2018.46036
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids Isolated from <i>Vitex grandifolia</i>, an Underutilized Vegetable, Exert Monoamine A & B Inhibitory and Anti-inflammatory Effects and Their Structure-activity Relationship

Abstract: Vitex grandifolia, Lamiaceae familyasına aittir; çiçekli bitkilerden oluşur ve aynı zamanda nane ailesi olarak da bilinir. Güneybatı Nijerya'daki Yoruba halkı bitkiyi "Oriri" veya "Efo oriri" olarak adlandırmaktadır. Bu bitki az kullanılan bir bitki olarak sınıflandırılır ve fitokimyası veya biyolojik etkileri hakkında çok az bilgi bulunmaktadır. Gereç ve Yöntemler: Kurutulmuş yaprak ve gövdelerden hazırlanan metanol ekstreleri üzerinde, vakum ve açık kolon kromatografısi metotları kullanılarak fraksiyonlama v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Bauhinia championii flavone scavenges free radicals and has an antiarrhythmic effect [ 89 , 90 ]. It improves mitochondrial dysfunction, alleviates H9C2 cardiomyocyte apoptosis induced by H/R, significantly inhibits ROS production, increases ATP synthesis, and inhibits abnormal mPTP opening.…”
Section: Hypoxiamentioning
confidence: 99%
“…Bauhinia championii flavone scavenges free radicals and has an antiarrhythmic effect [ 89 , 90 ]. It improves mitochondrial dysfunction, alleviates H9C2 cardiomyocyte apoptosis induced by H/R, significantly inhibits ROS production, increases ATP synthesis, and inhibits abnormal mPTP opening.…”
Section: Hypoxiamentioning
confidence: 99%
“…Over the years, people could notice the adverse effects of these pesticides made from chemicals, they are dangerous on plants, ecosystem, animals and humans. They are very toxic, non-biodegradable and posed hazards to farmers and non-target groups ( Chitwood, 2002 ; Oka et al., 2014 ; Bello et al., 2019a ).…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical constituents of leaves include flavonoids, saponins, cyanogenic glycosides, and terpenoids [10,14]. Recently, behavioral studies in mice have shown that the leaf extract of P. edulis f. flavicarpa displayed antidepressant-like activity, suggesting that this effect was correlated with the presence of C-glycosyl flavones [3,11,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Molecules of flavonoid O-glycosides need to be hydrolyzed in the stomach's acidic pH in order to be absorbed in the gastrointestinal tract. The C-glycosyl flavonoids, such as the antidepressant bioactive compounds from P. edulis [3,[15][16][17], are poorly absorbed in the gastrointestinal tract [7,12,13] because they need to be previously metabolized by the intestinal microbiota [7]. This fact, associated with the low aqueous solubility of aglycones, short elimination half-life, and rapid in vivo elimination of flavonoid glycosides, limits their clinical application [7,24,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation